A Review of Physical and Logical Design in IoT: Comparative Analysis of Devices, Protocols, Communication Models, and APIs - Akanksha Mishra (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Internet of Things (IoT) has emerged as a transformative technology, enabling connectivity and data exchange among a vast network of devices. This paper presents a comprehensive comparative analysis of the physical and logical design elements of IoT systems, focusing on IoT devices, communication protocols, models, and APIs (REST and WebSocket). The research highlights the critical role that both physical and logical components play in ensuring efficient, secure, and scalable IoT deployments. By examining the integration of these aspects, the paper aims to provide insights for optimizing IoT architectures for various use cases, particularly in resource-constrained environments.